Advances in the Development of Anti-Toxoplasma gondii Vaccines: Challenges, Opportunities, and Perspectives. Issue 3 (March 2019) - Wang, Jin-Lei; Zhang, Nian-Zhang; Li, Ting-Ting; He, Jun-Jun; Elsheikha, Hany M.; Zhu, Xing-Quan
Abstract : Important progress has been made in understanding how immunity is elicited against Toxoplasma gondii – a complex pathogen with multiple mechanisms of immune evasion. Many vaccine candidates have been tested using various strategies in animal models. However, none of these strategies has delivered as yet, and important challenges remain in the development of vaccines that can eliminate the tissue cysts and/or fully block vertical transmission. In this review, we provide an overview of the current understanding of the host immune response to T. gondii infection and summarize the key limitations for the development of an effective, safe, and durable toxoplasmosis vaccine. We also discuss how the successes and failures in developing and testing vaccine candidates have provided a roadmap for future vaccine development. Highlights: There is a compelling need to develop a safe and effective toxoplasmosis vaccine. Successful vaccination of domestic cats is the key step in reducing T. gondii transmission to humans and food-producing animals. An effective toxoplasmosis vaccine must be able to induce both humoral and cellular immune responses, directed against multiple different proteins, at different stages of the parasite life cycle. Live attenuated T. gondii strains offer good protection against toxoplasmosis, but the possibility of reversion to the virulent type remains possible. There is a need to identify more immunogenic antigens, adjuvants, and antigen-delivery systems together with defining robust immunocorrelates of protection. Having a standardized protocol for assessment of vaccine efficacy can facilitate the synergy between the results obtained by various research groups. 'Omics' technologies have revolutionized our understanding of the pathophysiology of toxoplasmosis, paving the way for development of a safe and effective vaccine.